Essential Role of IFN-γ in Regulating Gut Antimicrobial Peptides and Microbiota to Protect Against Alcohol-Induced Bacterial Translocation and Hepatic Inflammation in Mice - Yue, Ruichao; Wei, Xiaoyuan; Zhao, Jiangchao; Zhou, Zhanxiang; Zhong, Wei (Frontiers in Physiology, 2021)
The mechanisms by which alcohol provokes bacterial translocation in the development of alcoholic liver disease (ALD) remain incompletely defined. Our previous study demonstrates that impaired gut epithelial antimicrobial defense is critically involved in the pathogenesis of ALD. The study was set to determine the mechanisms of how alcohol inhibits the antimicrobial ability of intestinal epithelial cells (IECs) and to explore possible solutions to this issue. C57BL/6J mice were fed either alcohol or isocaloric dextrin liquid diet for 8 weeks, and intestinal IFN-γ-STAT signaling was analyzed. We found that chronic alcohol exposure led to a significant reduction in intestinal IFN-γ levels compared to control; the protein levels of phosphorylated signal transducer and activator of transcription 1 (p-STAT1) and p-STAT3 were both declined by alcohol. We then tested the effects of IFN-γ-STAT signaling on regulating antimicrobial peptides (AMPs), gut microbiota, and disease progression of ALD in mouse model of chronic alcohol feeding, time-course acute IFN-γ treatment, and in vivo and in vitro IEC-specific STAT1 or STAT3 knockout mouse models, respectively. Administration of IFN-γ activated intestinal STAT1 and STAT3, upregulated the expression of Reg3 and α-defensins, orchestrated gut microbiota, and reversed alcohol-induced intestinal ZO-1 disruption and systemic endotoxin elevation as well as hepatic inflammation. Meanwhile, acute IFN-γ treatment time-dependently induced AMP expression and α-defensin activation. We then dissected the roles of STAT1 and STAT3 in this progress. Lack of IEC-specific STAT3 inhibited IFN-γ-induced expression of Reg3 and α-defensins and hindered activation of α-defensins via inactivating MMP7, whereas lack of IEC-specific STAT1 impaired IFN-γ-stimulated expression of α-defensins and the IEC marker, sodium-hydrogen exchanger 3. Lastly, we found that interleukin (IL)-18, a known IFN-γ inducer, was also reduced by alcohol in mice. IL-18 treatment to alcohol-fed mice normalized gut IFN-γ levels and ameliorated organ damages in both the intestine and liver. Taken together, the study reveals that IFN-γ is critically involved in the regulation of AMPs through regulation of STAT1 and STAT3; impaired IFN-γ-STAT signaling provides an explanation for alcohol-induced gut antimicrobial dysfunction and microbial dysbiosis. Therefore, IFN-γ remains a promising host defense-enhancing cytokine with unexplored clinical potential in ALD therapy.